Who were the Nataruk people? Mandibular morphology among late Pleistocene and early Holocene fisher-forager populations of West Turkana (Kenya). Issue 121 (August 2018) - Mounier, Aurélien; Correia, Maria; Rivera, Frances; Crivellaro, Federica; Power, Ronika; Jeffery, Joe; Wilshaw, Alex; Foley, Robert A.; Mirazón Lahr, Marta
Abstract: Africa is the birthplace of the species Homo sapiens, and Africans today are genetically more diverse than other populations of the world. However, the processes that underpinned the evolution of African populations remain largely obscure. Only a handful of late Pleistocene African fossils (∼50-12 Ka) are known, while the more numerous sites with human fossils of early Holocene age are patchily distributed. In particular, late Pleistocene and early Holocene human diversity in Eastern Africa remains little studied, precluding any analysis of the potential factors that shaped human diversity in the region, and more broadly throughout the continent. These periods include the Last Glacial Maximum (LGM), a moment of extreme aridity in Africa that caused the fragmentation of population ranges and localised extinctions, as well as the 'African Humid Period', a moment of abrupt climate change and enhanced connectivity throughout Africa. East Africa, with its range of environments, may have acted as a refugium during the LGM, and may have played a critical biogeographic role during the heterogene`ous environmental recovery that followed. This environmental context raises a number of questions about the relationships among early Holocene African populations, and about the role played by East Africa in shaping late hunter-gatherer biological diversity. Here, we describe eight mandibles from Nataruk, an early Holocene site (∼10 Ka) in West Turkana, offering the opportunity of exploring population diversity in Africa at the height of the 'African Humid Period'. We use 3D geometric morphometric techniques to analyze the phenotypic variation of a large mandibular sample. Our results show that (i) the Nataruk mandibles are most similar to other African hunter-fisher-gatherer populations, especially to the fossils from Lothagam, another West Turkana locality, and to other early Holocene fossils from the Central Rift Valley (Kenya); and (ii) a phylogenetic connection may have existed between these Eastern African populations and some Nile Valley and Maghrebian groups, who lived at a time when a Green Sahara may have allowed substantial contact, and potential gene flow, across a vast expanse of Northern and Eastern Africa.